The Influence of Advertising, Brand Image, and Product Quality on Purchase Decisions of Skincare Beauty Products in Medan - Angela Callista Leonardi; Alfonsius, Alfonsius (Business and Entrepreneurial Review, 2024)
As time goes by, cosmetics have become one of the most important needs of women. In everyday life, women cannot be separated from cosmetics from morning to night, both face and body. In this current era, beauty products are increasingly diverse, and competition in the body care and cosmetics industry is fierce. At the same time, beauty and cosmetic products have undergone many changes, with various innovations that meet consumer needs and desires. This research aims to evaluate the influence of advertising, brand image, and product quality on purchasing decisions for skincare beauty products. The sample in this study consisted of 75 respondents, and the data analysis technique used was multiple linear regression. The research results showed that advertising, brand image, and product quality influence purchasing decisions for skincare beauty products. Partially, it showed that advertising has a significant influence on purchasing decisions, brand image has an important influence on purchasing decisions, and product quality influences purchasing decisions for skincare beauty products.